Haiti in the Time of Trash: Recycling, Rebuilding, and Remaining Joyful Five Years After the Earthquake - Khachadurian, Linda (2015)
The artists work with whatever materials they can pick up off the streets: metal, wood, nails, cracked CDs, tires, bottle caps and dismembered dolls. Eugène says that he’s partial to metal, which has become more and more difficult to find because of the clean-up initiative by the city. When I ask him if part of him wishes there were no such effort underway, he answers: “No. When you have clean streets you have good health, and that is the most important thing.”